Implementation of Qur’anic Learning through the Ilman wa Ruuhan Method at SMAIT Darul Ilmi Bandar Lampung - Angga Pratama; Septuri, Septuri; Meriyati, Meriyati; Ulfi Samaratul Jinan; Praniadi, Praniadi (al-Afkar, Journal For Islamic Studies, 2026)
Qur’anic learning is a pedagogical process aimed at developing students’ knowledge, skills, and attitudes through activities of reading and memorizing the verses of the Qur’an in a tartil manner properly and accurately in accordance with the rules of tajwid. One approach used in this process is the Ilman wa Ruuhan Method, which integrates scientific (cognitive) and spiritual (affective) dimensions. This study aims to analyze the implementation of the Ilman wa Ruuhan Method at SMAIT Darul Ilmi Bandar Lampung. The research adopts a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation, while data analysis employed an interactive model consisting of data condensation, data display, and conclusion drawing and verification. The findings indicate that Qur’anic learning through the Ilman wa Ruuhan Method is not only oriented toward improving students’ technical abilities in reading and memorizing the Qur’an, but also toward spiritual development that emphasizes the internalization of Qur’anic values in students’ daily lives. Therefore, this method is considered relevant for implementation in educational institutions because it integrates cognitive and affective aspects in a balanced manner. The findings contribute conceptually to the development of Qur’anic learning models oriented not only toward technical mastery but also toward the formation of students’ character and spirituality, and are expected to serve as a reference for similar institutions and further research.